Pengaruh Relaksasi Meditasi Gelembung Pikiran Terhadap Kecemasan Dalam Menghadapi Ujian Nasional Pada Siswa Sma/Sederajat Kelas Xii Di Tulungagung - Wardiana, Uswah; Rini, Afinia Sandhya (Happiness: Journal of Psychology and Islamic Science, 2019)
The research purpose is to find the effect of mind bubble relaxation meditation therapy to decrease anxiety level. The subject is senior high school students at XII grade who have anxiety level with intermediate and high category. The collecting data is done by using Hamilton Anxiety Rating Scale (HARS) that have had reliability and validity of 0, 93 and 0,97. This research used experimental method with one group pretest-posttest design. Statistic testing that used in this research is paired sample T-test toward experiment group with value of sig. (2-tailed) < 0, 05 or 0,000 < 0, 05. The result concluded that there is significance difference between pre-test result and post-test in the experiment group so there is a decreasing in subject anxiety after treated by mind bubble relaxation meditation therapy. All in all, there is an effect of giving relaxation mind bubble meditation therapy to decrease anxiety for senior high school students at XII grade toward national examination.